Congenital Rubella Syndrome: A Case Report - Deveci, Uğur; Gökcan, Filiz (Fırat University, 2007)
Rubella is a viral infection which cause chronic intrauterine infection and damage to the fetus. Congenital rubella syndrome is rare in the developed countries, however it is still a a major health problem in developing and under-developed countries. In this paper, we aimed to emphases a rarely case of congenital rubella syndrome and its morbidity. ©2007, Firat University, Medical Faculty

Kızamıkçık, kronik intrauterin enfeksiyona ve fetusta hasara neden olabilen viral bir enfeksiyondur. Doğumsal kızamıkçık sendromu gelişmiş ülkelerde çok nadir görülmesine karşın gelişmekte olan ve gelişmemiş ülkelerde hala önemli bir sağlık problemi olmaya devam etmektedir. Bu yazıda olgu sunumu ile birlikte doğumsal kızamıkçık sendromunun halen önemli bir morbidite nedeni olduğunun vurgulanması amaçlandı. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Doğumsal Kızamıkçık Sendromu: Olgu Sunumu